Rasionalisasi Perang Dagang Amerika Serikat dan Tiongkok Ditinjau dari Teori “Chicken Game” - Sebayang, Tino Rila; Kunkunrat, Kunkunrat; Irza, Apsha Lutvia; Pratama, Aditya Putra (Jurnal Ilmiah Hubungan Internasional, 2024)
This paper focuses on discussing the rationalization of the Trade War between the United States (US) and China from 2018 to 2022. The US and China action in the trade war were widely recognized as irrational, and given the negative impact on trade balance in both. The argument in this paper aims to prove that the protectionist policies of the both countries constitute a rational foreign economic strategic policy. The theory used to justify the aspect of rationality both uses Game Theory, namely the Chicken Game. On the other hand, the orientation of the Foreign Policy of the two countries which is considered rational, will be emphasized by the parameters of Cost and Benefit, by looking at the political motives being pursued for national interests by the US and China in the International Political Economy order. The methodology used in this paper is descriptive analysis, with a qualitative approach. The ideas to build arguments in this paper using previous literature reviews, with the narrative literature review method, according to relevant topics of discussion, concepts, and theories. On the other hand, as a justification for strengthening the parameters of the benefits of the both countries in the context of a trade war, this paper uses the Hegemonic Stability theory as benefit orientation for the US, as well as the Modified Structural theory from China's benefit perspectives. Keyword: Trade War; Cost and Benefit; Protectionism; Chicken Game; Foreign Economic Policy